UKRAINIAN KOZACS IN ART INTERPRETATION OF MYKOLA HOHOL’ AND PROSPER MÉRIMÉE - Matviishyn, V. G. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article deals with the issue of creative and critical cooperation between Mykola Hohol’ and Prosper Mérimée their private acquaintance in 1837 that contributed much to the French author’s interest in historical themes and his creation of both the historical tale «Bogdan Khmelnytskiy’» and the scientific research «Ukrainian Cossacks and Their Last Hetman’s».